An industrial perspective on counter anions in gold catalysis: on alternative counter anions - Schießl, Jasmin; Schulmeister, Jürgen; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
A comparison of versatile counter anions was investigated by means of a variety of well-known test reactions representing the key reactivity patterns of homogeneous gold catalysis, the catalytic activity was monitored by GC and 1H NMR. As previously reported, the counter anion influence is usually more pronounced than the corresponding ligand effect. Due to this, the study is focused on the investigation of counter anions so far not included from investigation of homogeneous gold-catalyzed reactions. The examinations using so far neglected counter anions (BArF4)−, [B(C6F5)4]−, [Al(OC(CF3)3)4]− and [B(C6F5)3(OAcF)]− showed surpassing or at least similar catalytic activities as the commonly used counter anions. The expanded use of counter anions can occupy an important role in future concerning catalyst optimization in gold catalysis.
Gesehen am 29.08.2018